2022
DOI: 10.3390/su14116446
|View full text |Cite
|
Sign up to set email alerts
|

Using Plastic Sand as a Construction Material toward a Circular Economy: A Review

Abstract: Recently, research on innovative approaches to and practices for plastic waste management in a circular economy has gained momentum. Plastic waste pollution poses a serious environmental concern. At the same time, the cement industry is among the biggest sources of CO2 emissions, which poses another environmental challenge. This makes plastic sand bricks an attractive alternative to concrete blocks and bricks. This paper looks at the recent studies regarding the development of plastic sand bricks and the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…1 depicts the development of plastic garbage from 1950 to 2019 [ 2 ]. The existing consumption patterns and methods of waste management will result in around 12,000 million tonnes of litter made of plastic being dumped in landfills and the natural environment by the year 2050, making it one of the most difficult kinds of pollution to eliminate [ 3 ]. Thus, there have been several initiatives worldwide, particularly in industrialised nations, to transform plastic trash into valuable items [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 depicts the development of plastic garbage from 1950 to 2019 [ 2 ]. The existing consumption patterns and methods of waste management will result in around 12,000 million tonnes of litter made of plastic being dumped in landfills and the natural environment by the year 2050, making it one of the most difficult kinds of pollution to eliminate [ 3 ]. Thus, there have been several initiatives worldwide, particularly in industrialised nations, to transform plastic trash into valuable items [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 It is important to note that several reported compressive strength value for PET and LDPE-sand bricks fall below 25 N/mm 2 . 13,[20][21] There is however report of up to 32.7 N/mm 2 compressive strength for LDPE-sand brick using sand grain size of 3 mm. 22 Based on sand classification by grain size, 3 mm sand grain size falls within coarse sand or sharp sand range.…”
Section: Introductionmentioning
confidence: 99%
“…22 Based on sand classification by grain size, 3 mm sand grain size falls within coarse sand or sharp sand range. 13 Our research however focuses on deployment of single use waste plastic from polyethylene terephthalate (PET) bottles and low density polyethylene (LDPE) films as a binder and sand of not more than 2 mm particle size (moderately coarse or medium sand) for production of IPB's with high compressive strength and very low water absorption percentage for application in street road construction especially in Nigeria. Sand has the capacity to improve the mechanical properties of plastics introduced as binding agent in sand-plastic composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that plastic wastes exceed 25 million tons per year, worldwide. Studies revealed that the use of plastic waste in construction materials resulted in a decrease in mechanical properties, but the density and the thermal conductivity of the new material decreased [15,16]. This would make the use of plastic wastes more attractive for the construction industry provided more research effort is invested in this direction.…”
mentioning
confidence: 99%